2013
DOI: 10.1158/0008-5472.can-12-4403
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/POU5F1/SOX2 Transcription Factor Complex Mediates IGF-I Receptor Signaling and Predicts Poor Prognosis in Lung Adenocarcinoma

Abstract: Cancer stem-like cells (CSLC) are crucial in tumor initiation and progression; however, the underlying mechanism for the self-renewal of cancer cells remains undefined. In the study, immunohistochemical analysis of specimens freshly excised from patients with lung adenocarcinoma showed that high expression of insulin-like growth factor I receptor (IGF-IR) in lung adenocarcinoma cells was positively correlated with the expressions of cancer stem cell markers CD133 and aldehyde dehydrogenase 1 family member A1 (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 52 publications
2
62
0
1
Order By: Relevance
“…CD133 expression is linked to a resistant phenotype in NSCLC and suggests that the detection of CD133 + cells may be useful to predict the efficacy of cytotoxic therapy for lung cancer (34). In addition, SOX2 expression maintained the self-renewal of lung cancer cells and was positively correlated with the metastatic progression of NSCLC (35,36), suggesting that CD133 and SOX2 expression plays an important role in studying the properties of cancer stem cells and the therapeutic response in lung cancer. Our study observed that SOX2 and CD133 expression were positively correlated with EGFR-TKI nonresponders and low expression levels of FOXO3a in lung cancer patients, and we found that NF-κB/miR-155 decreased FOXO3a expression to enhance CSC characteristics in vitro and in vivo, indicating that the NF-κB-driven suppression of FOXO3a plays a crucial role in CSC properties and EGFR-TKI resistance of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 expression is linked to a resistant phenotype in NSCLC and suggests that the detection of CD133 + cells may be useful to predict the efficacy of cytotoxic therapy for lung cancer (34). In addition, SOX2 expression maintained the self-renewal of lung cancer cells and was positively correlated with the metastatic progression of NSCLC (35,36), suggesting that CD133 and SOX2 expression plays an important role in studying the properties of cancer stem cells and the therapeutic response in lung cancer. Our study observed that SOX2 and CD133 expression were positively correlated with EGFR-TKI nonresponders and low expression levels of FOXO3a in lung cancer patients, and we found that NF-κB/miR-155 decreased FOXO3a expression to enhance CSC characteristics in vitro and in vivo, indicating that the NF-κB-driven suppression of FOXO3a plays a crucial role in CSC properties and EGFR-TKI resistance of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that SOX2 contributed to tumorigenesis and tumor progression of diverse cancers, including lung cancer [9], breast cancer [10], esophageal cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that aberrant expression of IGF-1R was correlated with tumor growth and poor prognosis in several human cancers such as myeloma[13] and breast cancer[14]. On the other hand, IGF-1R, as a hallmark of cell carcinogenesis, could also be regulated by transcription factors(TFs)[15], methylation[16] and microRNAs(miRNAs)[6, 17]. …”
Section: Introductionmentioning
confidence: 99%